Elimination of HIV in South Africa through expanded access to antiretroviral therapy: a model comparison study - Hontelez, Jan; Bärnighausen, Till; Baltussen, Rob M. P. M.; Tanser, Frank; Newell, Marie-Louise (PLoS medicine, 2013)
Using nine structurally different models, Jan Hontelez and colleagues investigate timeframes for HIV elimination in South Africa using a universal test and treat strategy. Please see later in the article for the Editors' Summary
Gesehen am 23.01.2018